ABDULLAH AHMAD AN-NA’IM DAN KONSEP PEMIKIRAN HUKUM LIBERALISNYA - Busyro, Busyro (Alhurriyah, 2014)
Abdullah Ahmad An-Na’im wants to understand Islam according to historical context at the time Islam all that rules were coming. The rule of Syaria, in every steps and in every period to ulama had proved that syaria was a kind of historical product which only compatible to the era, but there is no guarantee will be compatible for the modern era. Therefore, the way to understand syaria in this modern era is doing hermeunetic study, and it has proved that the An-Na’im theory has changed the understanding of the pioneer`s ulama and even rejecting all the rules which had been qath’i by the ulama before. Beside that, Abdullah is the one of the international fighter in humanism`s rights. He is really assure that for this time syaria should be understand in international rights`s context. It is exist to create the equality and the widely acceptance in international world to existence of Islam with its syaria.